Pengaruh Penambahan Lisin dalam Ransum terhadap Berat Hidup, Karkas dan Potongan Karkas Ayam Kampung - A. Yuniza; Nuraini Nuraini; S. Hafiz (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
Standard of nutrient requirements especially amino acid requirements in kampung chicken’s diet was not known yet. Therefore, until now formulation of kampung chicken’s diet still refferenced to nutrient requirements of laying hen. Usualy formulation of kampung chicken was based on protein and metabolizable energy requirement only, without considering about it’s balances of amino acids. Amino acids that usualy deficiency in diet were lysine and methionine. Because, study about amino acid requirement of kampung chicken was limited, so this research was conducted to study effect the suplementation of lysine in kampung chicken diet on body weight, carcass, and carcass quarter of kampung chicken (thigh and breast quarter yield). The experiment was designed by using randomized completely design with 5 treatments of supplementation of lysine (A = 0 % as a control, B = 0.15%, C = 0.30%, D = 0.45%, and E = 0.60%) in diet which crude protein content 14.5% and 2900 kkal/kg ME with 4 replications. Parameters were: body weight, carcass weight, percentage of carcass, thigh weight, breast weight, percentage of thigh, and percentage of breast of kampung chickens. The results showed that suplementation of lysine in diet highly significant (P<0.01) increased the body weight, carcas weight, thigh weight and breast weight. Suplementation of lysine in diet also significant (P<0.05) increased the percentage of breast, but not significant (P>0.05) on persentage of carcas and percentage of thigh. Levels supplementation of lysine bigger than 0.15% in diet (C = 0.30%, D = 0.45%, and E = 0.60%) gave the same effect as at level 0.15%. It concluded, the level of lysine supplementation in kampung chicken diet recomended was 0.15%. Therefor it was known that requirement lysine for kampung chicken on growth periode was 0.77%.